System-information mechanisms of the psyche and consciousness - Оноприенко, Ю. И. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2017)
The nature and mechanisms of the psyche and consciousness are explored on the basis of the author's concept of system-information methodology. Much attention is paid to the problem of myth-making which is the key one in the analysis of consciousness.